2020
DOI: 10.14245/ns.2040040.020
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a and wnt5a as Potential Chondrogenic Stimulators for Nucleus Pulposus Cell Induction: A Comprehensive Review

Abstract: Low back pain remains a highly prevalent pathology engendering a tremendous socioeconomic burden. Low back pain is generally associated with intervertebral disc (IVD) degeneration, a process involving the deterioration of nucleus pulpous (NP) cells and IVD matrix. Scientific interest has directed efforts to restoring cell numbers as a strategy to enable IVD regeneration. Currently, mesenchymal stromal cells (MSCs) are being explored as cell therapy agents, due to their easy accessibility and differentiation po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 98 publications
(170 reference statements)
1
9
0
Order By: Relevance
“…Overall, the activation of the pathway plays a critical role in cell fate decisions, notably for MSC proliferation, self-renewal and differentiation. In particular, Wnt signaling modulation in MSCs is widely investigated to fully exploit regenerative properties of MSCs in different research fields, such as bone, lung, and heart biology ( Volleman et al, 2020 ). The canonical Wnt/β-catenin pathway sustains proliferation and renewal of MSCs; therefore, the use of pharmacological modulators of the pathway has brought several informations.…”
Section: Wnt Signaling In Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the activation of the pathway plays a critical role in cell fate decisions, notably for MSC proliferation, self-renewal and differentiation. In particular, Wnt signaling modulation in MSCs is widely investigated to fully exploit regenerative properties of MSCs in different research fields, such as bone, lung, and heart biology ( Volleman et al, 2020 ). The canonical Wnt/β-catenin pathway sustains proliferation and renewal of MSCs; therefore, the use of pharmacological modulators of the pathway has brought several informations.…”
Section: Wnt Signaling In Mscsmentioning
confidence: 99%
“…One key mechanism of the suppressive role of Wnt/β-catenin on adipogenesis is the reduced expression of adipogenic transcription factors CCAAT/enhancer binding protein alpha (C/EBPalpha) and peroxisome proliferator-activated receptor gamma (PPARgamma) ( Ross et al, 2000 ; Yuan et al, 2016 ). However, the use of Wnt/β-catenin inhibitors, such as Quercitin, reduce MSC proliferation and multipotency by favoring their osteogenic commitment and inhibiting both the chondrogenic and the adipogenic differentiation ( Qu et al, 2013 ; Narcisi et al, 2015 ; Jothimani et al, 2020 ; Volleman et al, 2020 ). This model failed to explain the positive contribution of canonical Wnt in bone homeostasis in vivo ( Wagner et al, 2020 ).…”
Section: Wnt Signaling In Mscsmentioning
confidence: 99%
“…A recent literature review [48] suggested the potential ability of Wnt3a to maintain the differentiation potency of MSC as opposed to inducing chondrogenic differentiation, which could help explain the discrepancies in monolayer and pellet culture outcomes. To test this hypothesis, we applied Wnt3a at 250 ng mL −1 during the MSC (n = 1, 23-year-old) expansion culture and subsequently subjected these cells to chondrogenic pellet culture supplemented with GDF5/TGF-β1 or commercial pre-defined Mesenchymal Stem Cell Chondrogenic Differentiation Medium (Chon.M.…”
Section: Wnt3a Mediated Pre-conditioningmentioning
confidence: 99%
“…In their work, they found that only combined application of TGF-β1 and GDF5 was able to create MSC that formed fully chondrogenic pellets, as well as stringently enhance expression of NP cell markers; e.g., ACAN, COL2A1, CD24, PAX1, and OVOS2. Review work has also suggested the application of both Wnt3a or Wnt5a as promising chondrogenic factors, particularly combining Wnt3a with other chondrogenic factors was speculated to hold potential [48]. A wide range of factors has been proposed to enable MSC to NP cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the WNT pathway plays a critical role in cell fate decisions, particularly for MSC proliferation, self-renewal and differentiation. Furthermore, WNT signaling modulation in MSCs has been widely investigated to fully exploit the regenerative properties of MSCs in different fields, such as bone, lung and heart biology ( 32 , 33 ). Our previous study also demonstrated that a decreased expression level of the WNT pathway during periodontitis and overactivation may rescue periodontal tissue loss.…”
Section: Introductionmentioning
confidence: 99%